2013
DOI: 10.1007/s10329-013-0367-1
|View full text |Cite
|
Sign up to set email alerts
|

What makes wild chimpanzees wake up at night?

Abstract: I examined the possible cause of night awakening among wild chimpanzees (Pan troglodytes) in Mahale Mountains National Park, Tanzania. Chimpanzee vocalizations and activity-related sounds (CVSs) were used to indicate awakening because I was unable to visually observe them. Over a 5-night observation period, CVSs (n = 128) were heard every night, and most (n = 91) were observed within 5 min of previous CVSs. Chimpanzees use CVSs as social communication to maintain spatial contact with other chimpanzees who occa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 40 publications
(26 reference statements)
0
29
0
Order By: Relevance
“…I began data collection when low‐light conditions required using a flashlight (with red bulb) to write. Unlike Zamma (), I did not use chimpanzees’ nesting behavior as an indication to start data collection on nocturnal behavior, as Fongoli chimpanzees often nested well after dark, especially during the dry season. Therefore, data collection included behavior that occurred before nesting began but after darkness fell as well as behavior following nesting, presumed sleeping and then waking.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…I began data collection when low‐light conditions required using a flashlight (with red bulb) to write. Unlike Zamma (), I did not use chimpanzees’ nesting behavior as an indication to start data collection on nocturnal behavior, as Fongoli chimpanzees often nested well after dark, especially during the dry season. Therefore, data collection included behavior that occurred before nesting began but after darkness fell as well as behavior following nesting, presumed sleeping and then waking.…”
Section: Methodsmentioning
confidence: 99%
“…Reports of nocturnal activity by wild, diurnal primates are mainly anecdotal and include reports of vocalizations as well as activity such as foraging or traveling. Numerous studies have reported nocturnal movement for diurnal primates ( Alouatta pigra : Dahl & Hemingway, ; Cebus capucinus : cited in Bearder et al, ; Theropithecus gelada : Kawai & Iwamoto, ; Macaca mulatta : Vessey, ; M. fuscata : Nishikawa & Mochida, ; M. sinica : cited in Bearder et al, ; Pongo pygmaeus : MacKinnon, ; Pan troglodytes : Goodall, ; Pruetz & Bertolani, ; Zamma, ) as well as diurnal strepsirhines ( Lemur catta : Donati et al, 2013). Primates heard vocalizing at night include Barbary macaques ( M. sylvanus : Hammerschmidt et al, ) and chimpanzees (Goodall, ; Izawa & Itani, ; Tutin et al, ), and gorillas ( Gorilla beringei ) chest‐beat at night (Schaller, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the study reporting this volume did not specify how this value was acquired, it is possible that this value represents defecations only during the daytime and does not include those at night. A recent study of nighttime behaviors of Mahale chimpanzees (Zamma 2014) revealed that they frequently defecate at night-even at midnight. If we calculate chimpanzee defecations using V obs and the average number of seeds contained in a fecal clump, the estimate is 11.8 defecations 24 h -1 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been noted that the forager pattern may be polyphasic [50,51]; even preindustrial, preelectric western populations divided the night into "first sleep" and "second sleep, " indicating a polyphasic pattern [52]. Chimpanzees night-time vocalizations at Mahale have been recorded to be especially active during the periods of 23:00-02:00, with a predominance of pant-hoots associated with night-time defecation and urination [53]. With respect to orangutans, it may also be the case that the cost of night-time vocalizations can be made up during the day with "siesta napping, " which has been observed in all ape populations [54] and is characteristic of equatorial forager's daily inactivity patterns [55,56].…”
Section: Advances In Zoologymentioning
confidence: 99%